Relaxations of perturbations of spacetimes in general relativity coupled to nonlinear electrodynamics - Bobir Toshmatov; Zdeněk Stuchlík; Bobomurat Ahmedov; Daniele Malafarina (My University, 2019)
Three well-known exact regular solutions of general relativity coupled to nonlinear electrodynamics (NED), namely the Maxwellian, Bardeen, and Hayward regular spacetimes, which can describe either a regular black hole or a geometry without horizons, have been considered. Relaxation times for the scalar, electromagnetic (EM) and gravitational perturbations of black holes and no-horizon spacetimes have been estimated in comparison with the ones of the Schwarzschild and Reissner-Nordström spacetimes. It has been shown that the considered geometries in general relativity coupled to the NED have never-vanishing circular photon orbits, and on account of this fact these spacetimes always oscillate the EM perturbations with quasinormal frequencies. Moreover, we have shown that the EM perturbations in the eikonal regime can be a powerful tool to confirm (i) that the light rays do not follow null geodesics in the NED by the relaxation rates and (ii) if the underlying solution has a correct weak field limit to the Maxwell electrodynamics by the angular velocity of the circular photon orbit.
Keywords: regular black holes; nonlinear electrodynamics; perturbations; quasinormal frequencies; relaxation times; Maxwellian; Bardeen; Hayward; no-horizon spacetimes